2018
DOI: 10.1177/1040638718767943
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Tritrichomonas foetus molecular testing

Abstract: Bovine trichomoniasis is a sexually transmitted disease that results in infertility, abortion, and calf age variability. To date, management strategies include testing for Tritrichomonas foetus and culling of infected males. Challenges associated with testing include cost of culture medium, time and labor burden of sample incubation and processing, and adverse effects of bacterial growth on detection sensitivity. To overcome these challenges, we developed a direct reverse-transcription quantitative real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 16 publications
0
29
1
Order By: Relevance
“…A North American study showed that quantitative real-time PCR (RT-qPCR) presented 100% sensitivity and specificity for smegma samples. In comparison, PCR analysis of culture aliquots showed 5% less sensitivity (Ginter Summarell et al, 2018). Therefore, new techniques and methodologies may obtain a different result than the one obtained in the present study.…”
Section: Arqcontrasting
confidence: 81%
See 1 more Smart Citation
“…A North American study showed that quantitative real-time PCR (RT-qPCR) presented 100% sensitivity and specificity for smegma samples. In comparison, PCR analysis of culture aliquots showed 5% less sensitivity (Ginter Summarell et al, 2018). Therefore, new techniques and methodologies may obtain a different result than the one obtained in the present study.…”
Section: Arqcontrasting
confidence: 81%
“…The samples for the present study were chosen because they had not yet been surveyed for T. foetus. In addition, other studies have shown that PCR can have better results when performed directly with pure samples rather than with culture samples (Ginter Summarell et al, 2018). Since it was not possible to use the parabasalid in vivo, we employed a previously extracted DNA sample as positive control.…”
Section: Arqmentioning
confidence: 99%
“…Another method is by inoculating the parasite in different types of culture media., this method takes from two to seven days and does not differentiate between the different types of Tritrichomnas spp. (6). Further, the serological test can be used for diagnosis of the parasite such as mucus agglutination test and ELISA test, but these tests have limited use because of low sensitivity, the specificity of tests, and in bulls do not develop tangible immune responses (7).…”
Section: Introductionmentioning
confidence: 99%
“…Samples had been stored at −20°C prior to use in our study. To evaluate the updated workflow, 20 individual T. foetus– positive samples were extracted, in triplicate, and tested using both the previously described workflow 8 and the new workflow, which utilized a commercial extraction kit (MagMAX CORE nucleic acid purification kit) and a newer master mix chemistry (TaqMan fast virus 1-step master mix). Total nucleic acid was extracted following the manufacturer’s instructions.…”
mentioning
confidence: 99%